Health Initiatives Vitalize - Keith V. Bletzer (Issues and Development in Health Research Vol. 3, 2021)
This chapter reviews initiatives in HIV/AIDS surveillance, as performed by health departments within the United States in collaboration with the Centers for Disease Control and Prevention. The first objective is a historic analysis that emphasizes the expansion of HIV Surveillance Reports, which have served as the main source of information from the Centers for Disease Control and Prevention on the impact of HIV/AIDS over the past four decades in the United States and its eight independent areas. A second objective is a procedural examination of the role of state health departments through active surveillance that contributes to the accuracy and functionality of HIV/AIDS data in HIV Surveillance Reports. The chapter is an expanded, revised version of Bletzer [1].